Genotyping of ticks: first molecular report of Hyalomma asiaticum and molecular detection of tick-borne bacteria in ticks and blood from Khyber Pakhtunkhwa, Pakistan - Obaid, Muhammad Kashif; Shehla, Shehla; Guan, Guiquan; Rashid, Muhammad; Shams, Sumaira (Frontiers in Cellular and Infection Microbiology, 2024)
Multiple ticks (Acari: Ixodoidea) carrying Rickettsiales bacteria have significant importance for both human and animal health. Thus, the purpose of this work was to genetically analyze tick species and their associated Rickettsiales bacteria in animal hosts. In order to achieve these objectives, various animals (including camels, cattle, goats, sheep, dogs, and mice) were inspected in four districts (Mardan, Peshawar, Kohat, and Karak) of Khyber Pakhtunkhwa to collect ticks, while blood samples were collected from all the symptomatic and asymptomatic cattle in all four districts. A total of 234 ticks were obtained from 86 out of 143 (60.14%) host animals, which were morphologically identified as Rhipicephalus turanicus, Rhipicephalus microplus, Haemaphysalis cornupunctata, and Hyalomma asiaticum. Among these, their representative ticks (126/234, 53.85%) were processed for molecular confirmation using cytochrome c oxidase (cox1) gene. Obtained cox1 sequences of four different tick species showed 99.72%–100% maximum identity with their corresponding species reported from Pakistan, China, India, and Kazakhstan and clustered phylogenetically. This study presented the first genetic report of Hy. asiaticum ticks in Pakistan. Moreover, genetically confirmed tick species were molecularly analyzed by PCR for detection of Rickettsiales DNA using partial fragments of 16S rDNA, 190-kDa outer membrane protein A (ompA), and 120-kDa outer membrane protein B (ompB) genes. In addition, blood samples were analyzed to identify Rickettsiales bacteria using the aforementioned genes. Rickettsiales bacteria were found in 24/126 (19.05%) ticks and 4/16 (25.00%) in symptomatic cattle’s blood. The obtained ompA and ompB sequences from Hy. asiaticum ticks showed 99.73%–99.87% with Candidatus Rickettsia shennongii and unidentified Rickettsia sp., whereas the obtained 16S rDNA sequences from cattle’s blood and ticks (Hae. cornupunctata) showed 99.67% highest identity with Anaplasma phagocytophilum. The 16S rDNA sequence of Rickettsiales DNA from Rh. turanicus ticks showed 100% identity with Ehrlichia canis and unidentified Ehrlichia sp. Obtained sequences of Rickettsiales bacteria were grouped along with their respective species in phylogenetic trees, which were previously reported in Greece, Cuba, Iraq, Turkey, Pakistan, South Korea, and China (mainland and Taiwan). This extensive study explores the wide range of damaging ticks and their corresponding tick-borne bacteria in the area, suggesting a possible danger to both livestock and human communities.